S-42-3: HIV INFECTION AND ANTIRETROVIRAL THERAPY ARE ASSOCIATED WITH INCREASED ARTERIAL STIFFNESS: A SYSTEMATIC REVIEW AND META-ANALYSIS. (January 2023) - Defo, Alvin Kuate; Chalati, Mhd Diaa; Labos, Christopher; Fellows, Lesley K; Mayo, Nancy E; Daskalopoulou, Stella S
Abstract : Objective: Incidence of cardiovascular disease (CVD) in people living with human immunodeficiency virus (HIV) infection has increased as overall survival has improved due to combination antiretroviral therapy (cART). Arterial stiffness is a composite indicator of CVD risk independent of traditional risk factors. We therefore aimed to synthesize the evidence on the effect of HIV and of cART on arterial stiffness. Design and Methods: We conducted a systematic review of Medline/PubMed, Embase, CINAHL, and the Cochrane Library, searched independently by two reviewers using a predefined search strategy, for studies relating HIV/cART to arterial stiffness until June 2019. Studies were limited to humans and publication in English or French. A standardized extraction form was used to collect data from published reports. Random-effects meta-analyses were performed to produce standardized mean differences (SMDs) and 95% confidence intervals (CIs) from studies reporting carotid-femoral pulse wave velocity. Results: We retrieved 995 citations. Seventy-four studies (N = 18, 711 participants/13, 119 with HIV) were included: 59 cross-sectional, 9 cohort studies and 6 randomized controlled trials. In meta-analyses of 17 studies, arterial stiffness was found to be increased overall in individuals with HIV relative to healthy controls (SMD 0.44 m/s; 95% CI, 0.25–0.63) and in cART-treated versus untreated individuals with HIV (SMD 0.35 m/s; 95% CI, 0.13–0.57). Several studies suggested that cumulative exposure to cART is associated with a continual increase in arterial stiffness. However, early initiation of treatment might improve arterial stiffness later in life by negating the effect of the HIV. Conclusions: Evidence suggests that HIV infection is associated with increased arterial stiffness, while cART is linked to a further increase, highlighting the need for monitoring of CVD risk in this population, and the need for development of novel treatments. The cross-sectional nature of most studies (59/74) mainly allowed for the exploration of associations. Large longitudinal studies are needed to confirm the observed relationships and establish causality between HIV/cART and arterial stiffness.